"Historical Culture in Museums: The Representations of the First World War in the 'Historial De La Grande Guerre' Museum of France & in the Imperial War Museum of London". Issue 2 (1st July 2016) - Korres, Kostas; Kokkinos, George
Abstract : The year 2014 marked a century since the outbreak of the First World War (1914–1918) in Europe. This war "was perhaps the first major trauma of modern Europe" and the womb from which were born the bad consequences that affected the 20th century modern world, according to the historian Jay Winter. Due to the centenary of the Great War, the museums of war of various states in Europe have openings of special exhibitions, using also new technologies as means of informal education of their audience.In our research, we critically exam the different representations of WW1 and their museological variations in two of the most important museums of war in Europe, the Imperial War Museum in London and the Historial de la Grande Guerre in France.Furthermore, we examine whether the use of new technologies supports the interdisciplinary approach of history and cultivates a holistic, multifaceted and critical historical culture, which is utilized under the fruitful informal educational environment of the museum.In particular, the purpose of our research is(a) to distinguish the different approaches in the museological representations of WW1 – traditional, modern and postmodern – and(b) to determine their connection to the respective approaches of history and with different educational practices, addressing specific ways of "narrative" and "reading" of that historical period. The methodology is qualitative research, an ethnographic on-site observation in the museums.In other words, we are interested especially if the public history that museums offer as historical culture to their audience, converges or diverges from scientifically valid historical truth, and whether it contributes to the completion of the collective mourning process, bringing together the historical truth with universal historical importance fact of WW1 to a new historical awareness and favors the desire for peaceful coexistence of all European people.